The Role of Challenge in Talent Development: Understanding Impact in Response to Emotional Disturbance - Jamie Taylor; Michael Ashford; Dave Collins (Psych, 2022)
(1) Background: The pursuit of excellence is central to most development environments, and this is particularly the case in high-performance sport. Accordingly, we examined some mechanisms for development, focusing on the nature and impact of challenge in the experiences of more or less successful high-level rugby players. (2) Methods: Retrospective interviews were conducted with two groups of players. All had been successful on the development pathway (i.e., recruited to high level academies and selected as age group internationals). Only some had progressed to senior contracts and international selection, offering a basis for contrast. (3) Results: Data suggest the importance of negative experiences in the development of performers and performance. Importantly, however, the impact is dependent on both the skills of the individual and the style, timing and context of the challenge. (4) Conclusions: Negative experiences seemed to offer developmental opportunities wider than just learning to cope, at least for those who eventually succeeded. In short, progress was dependent on an interaction between individual skill, interpretation, context and social setting. The need for coaches and others to develop the appropriate attitudes and approach to challenge is a clear implication.